Aplikatif Sistem Agroforestri Pada Tanaman Umbi-umbian Lokal dan Kemiri dalam Upaya Peningkatan Pendapatan - Hendra Pribadi; Syukur Umar; Sudirman Dg. Massiri; Abdul Muis; Sri Jumiyati; I Ketut Widnyana; Jamila Mustabi; Frizkiawan I Sompalele (Madani : Indonesian Journal of Civil Society, 2022)
Optimizing farmers' income can be done by optimizing land use, namely the agroforestry system, the problem is that the community has not applied the agroforestry system to their land on the grounds that plants growing understands will not produce maximum production. For this reason, it is necessary to carry out training activities for planting an agroforestry system for candlenut plants and tubers. Local tubers and candlenuts. The method used is firstly observing the location of the land that will be used as a training ground, secondly carrying out training activities on agroforestry systems by paying attention to the fertilizers used, the model beds. Which is made. The results of the training show that people who initially only planted tubers on open land would plant them under the candlenut plant. Enthusiastic in participating in the activity and there is also an increased understanding of the agroforestry system, this agroforestry training activity is important to optimize land use and increase farmers' income.